Serratia marcescens and its role in Pink breast milk and upper GI bleeding in an infant: a Tanzanian case report - Rukhsar Osman; Mayila Mbuki; Hajaj Salum; Mohamedraza Ebrahim; Maria Bulimba; Nahida Walli; Jonathan A. Shogholo; Masolwa D. Ng’wanasayi; Mariam Noorani (BMC Infectious Diseases)
Abstract Background Serratia marcescens, a gram-negative bacterium once considered non-pathogenic, is now recognized as a cause of hospital-acquired infections, particularly in immunocompromised patients with outbreaks reported in neonatal intensive care units. In newborns, it can result in severe illness, including sepsis and meningitis. It is well recognized by the production of pink pigment found on drains and other equipment, including breast pumps. Case report We report a case of a two-month-old previously healthy infant with upper gastrointestinal bleeding, whose mother had pink-stained expressed breast milk. Cultures of the breast milk and gastrointestinal aspirates of the infant grew S. marcescens. The infant received proton pump inhibitors, blood transfusions, and antibiotics, with successful resolution of the bleeding. Conclusion S. marcescens should be considered a potential cause of gastrointestinal bleeding in infants at risk. Although previously known to cause outbreaks in vulnerable infants, pathogenicity in healthy infants is also possible. Maintaining strict hygiene of feeding and breast milk pumping equipment is important to prevent infections in infants.